2009
DOI: 10.1128/jcm.00805-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cavidi ExaVir Load Assay (Version 3) for Plasma Human Immunodeficiency Virus Type 1 Load Monitoring

Abstract: We evaluated the new low-cost ExaVir Load (version 3) reverse transcriptase viral load assay against the Roche Cobas Amplicor assay. Results for samples tested using the reverse transcriptase assay correlated well with those obtained with the Roche assay (r ‫؍‬ 0.85; n ‫؍‬ 202). The version 3 reverse transcriptase assay shows improved sensitivity compared to the previous version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 19 publications
(22 reference statements)
4
23
0
Order By: Relevance
“…However, later reports showed no association between the presence of RT inhibitors or resistance mutations with differences between RT activity and HIV-1 RNA in the plasma (23,29,32,57,58). Although our study was not designed to investigate the effect of RT inhibitors on the performance of ExaVir Load in HIV-2 infection, our results agree with these reports since no significant differences were found between viral load measurements with ExaVir Load or qPCR in treated and untreated patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, later reports showed no association between the presence of RT inhibitors or resistance mutations with differences between RT activity and HIV-1 RNA in the plasma (23,29,32,57,58). Although our study was not designed to investigate the effect of RT inhibitors on the performance of ExaVir Load in HIV-2 infection, our results agree with these reports since no significant differences were found between viral load measurements with ExaVir Load or qPCR in treated and untreated patients.…”
Section: Discussionsupporting
confidence: 79%
“…This characteristic, and its low cost, simplicity to operate, and commercial availability make it an attractive option for monitoring the HIV viral load in countries with limited resources. Indeed, ExaVir Load assay versions 1 (26,31), 2 (24,28,29,32,33), and 3 (23,29,34), with sequentially improved sensitivity and shorter turnaround times (34,35), have been used in many resource-limiting settings, in Asia and in Africa, to monitor the viral load in HIV-1-infected pediatric and adult patients undergoing antiretroviral treatment. Overall, measurements with the ExaVir Load assay showed good agreement with "goldstandard" HIV-1 viral load assays, such as Abbott M2000sp/M2000rt RealTime HIV-1 (23,30), Roche Amplicor HIV-1 Monitor (24,25,27,28,33,36), Roche Cobas Amplicor (29,30,32,34,37), Versant Bayer HIV-1 bDNA (22,33), and bioMérieux NucliSense HIV-1 QT (26).…”
mentioning
confidence: 99%
“…Results from the bDNA 3.0 showed much lower levels of discordance compared to the Amplicor 1.5, with between 2–26% of results having clinically important differences [22], [27]. Only one study reported differences between results from the ExaVir v3.0 and the Amplicor v1.5; in this study, 27% of results from the ExaVir differed by more than 0.5log 10 [28].…”
Section: Resultsmentioning
confidence: 49%
“…The Exavir™ Load, an enzyme-linked immune-sorbent assay (ELISA)-based VL quantification test (Cavidi AB, Uppsala, Sweden [23, 24]), was used in Vietnam for the first time to monitor the virologic outcomes for all participants every 6 months for 24 months of the study. The detection limits range from 200 to 410,000 copies/ml [25].…”
Section: Methodsmentioning
confidence: 99%